2019
DOI: 10.1088/1757-899x/660/1/012031
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Silica Fume Addition on the Resistance of Concrete to Alkali Silica Reaction

Abstract: Concrete mix made of cement CEM I 42.5 R, silica fume, fine aggregate sand of 0/4 fraction and superplasticizer was tested. Five batches of specimens were made with different silica fume content, where up to 10 % of the binding material was replaced with silica fume. Compressive strength, water absorption, density and resistance to alkali silica reaction were tested in concretes modified with different amounts of silica fume addition. The effect of silica fume addition on the expansion of modified concrete con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
0
0
1
Order By: Relevance
“…The porosity of the x = 0.7 sample in this work was close to the porosity value of the HAP + Mg/CSH bone cement (∼44-46%) observed previously by Zima et al 29 These results suggested that the x = 0.7 or HAP-0.7CaS bone cement had the highest density and hence lowest porosity and lowest water absorption values. This result was also consistent with the previous work studied by Nagrockienė et al 65 They also reported that when silica fume lled in small voids in concrete structures, it became more homogeneous, and the density increased, whereas the porosity and water absorption values decreased.…”
Section: Physical Properties and Water Absorptionsupporting
confidence: 93%
“…The porosity of the x = 0.7 sample in this work was close to the porosity value of the HAP + Mg/CSH bone cement (∼44-46%) observed previously by Zima et al 29 These results suggested that the x = 0.7 or HAP-0.7CaS bone cement had the highest density and hence lowest porosity and lowest water absorption values. This result was also consistent with the previous work studied by Nagrockienė et al 65 They also reported that when silica fume lled in small voids in concrete structures, it became more homogeneous, and the density increased, whereas the porosity and water absorption values decreased.…”
Section: Physical Properties and Water Absorptionsupporting
confidence: 93%
“…The rice husk volume fraction of 20% resulted in an increase in the silica content of the composite specimens. The higher silica content results in an increase in the density of the composite due to lower water absorption [25].…”
Section: Resultsmentioning
confidence: 99%
“…Pada aerated concrete mengalami peningkatan berat jenis seiring dengan peningkatan persentase penggunaan silica fume. Penambahan silica fume sebesar 10% berdasarkan berat semen meningkatkan densitas, kuat tekan, dan mengurangi penyerapan air (Nagrockienė et al, 2019).…”
Section: Pengujian Berat Jenisunclassified